Pemanfaatan RCA, GGBS dan FA sebagai Bahan Substitusi Campuran Beton Ramah Lingkungan - Aep Saepuloh; Ade Suhendar S. (Jurnal Sains dan Teknologi (JSIT), 2026)
Industrial and construction waste has become a major environmental issue that contributes to ecosystem degradation, increased carbon emissions, and excessive exploitation of natural resources in the construction sector. Continuous use of cement and natural aggregates also increases energy consumption and environmental damage caused by construction material mining activities. This study aims to analyze the utilization of Recycled Concrete Aggregate (RCA), Fly Ash (FA), and Ground Granulated Blast-Furnace Slag (GGBS) as substitution materials in environmentally friendly concrete mixtures and to evaluate their effect on concrete compressive strength. The research employed a quantitative experimental method referring to SNI 7656:2012 for concrete mix design and SNI 1974:2011 for compressive strength testing. RCA was used as a partial substitute for coarse aggregate, while FA and GGBS were used as partial substitutes for cement. Data analysis was carried out descriptively and quantitatively by comparing the compressive strength results of normal concrete and substituted concrete at the ages of 3, 7, 14, and 28 days using cylindrical specimens. The results showed that normal concrete achieved an average compressive strength of 67.01 MPa at 28 days, while substituted concrete achieved 45.72 MPa. Although the compressive strength of substituted concrete was lower than that of normal concrete, the strength continued to increase with curing age. The utilization of RCA, FA, and GGBS has the potential to reduce the use of natural materials, minimize carbon emissions, and support sustainable construction practices.